Mechanical behavior of cylindrical GFRP chimney liners subjected to axial tension. (15th November 2019) - Cheng, Shi; Feng, Peng; Li, Zhiyuan; Du, Jike
Abstract: The large diameter filament-wound glass fiber reinforced polymer (GFRP) tube as the chimney liner is a pivotal anti-corrosion structure in the wet flue gas desulfurization system. Fourteen GFRP specimens with a larger size (3000 mm × 1100 mm × 5.6 mm) and twenty GFRP specimens with a smaller size (350 mm × 25 mm × 5.6 mm) have been investigated by tensile tests. All specimens were cut from two GFRP chimney liner specimens, which were fabricated with the scaled-down ratio of 3:1 (practical to experimental) according to the standard guide for design of GFRP chimney liners for coal-fired units. Among the fourteen larger specimens, seven specimens were cut into two segments and then jointed by the hand-wound technique at the middle height of the specimens, while the other seven larger specimens and twenty smaller specimens were integrated. All specimens were subjected to axial tension at four different temperatures, including the ambient temperature (approximately 30 °C), 60 °C, 90 °C, and 120 °C. Based on the tests, the failure modes and tensile load-displacement relationships were determined. The temperature-dependency and size-dependency of the tensile strength, tensile strain, and elastic modulus were analyzed. Moreover, the comparisons between integrated and jointed specimens were examined. Finally, a modeling method for the tensile mechanical properties of composites under elevated temperatures was proposed for GFRP chimney liner design.